2005
DOI: 10.1002/elps.200410398
|View full text |Cite
|
Sign up to set email alerts
|

On-line pervaporation-capillary electrophoresis for the determination of volatile acidity and free sulfur dioxide in wines

Abstract: Pervaporation has been coupled on-line to capillary electrophoresis (CE) by a simple interface consisting of a modified CE vial. The approach allows volatile analytes to be removed and injected into the capillary meanwhile the sample matrix remains in the pervaporator. By this approach volatile acidity and free sulfur dioxide have been simultaneously determined in wines. The detection limits (LODs) are 1.25 and 5.00 microg/mL, the quantification limits 4.12 and 16.50 microg/mL, and the linear dynamic ranges be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Pervaporation has been coupled online to CE using a simple interface (a modified CE vial) that allowed volatile analytes (e.g., HSO À 3 ) to be isolated and interferences from complex matrices thus avoided [88]. Another option when the performance of a CE system can be improved at the stage of sample introduction concerns the application of flow injection (FI)-CE systems [89].…”
Section: Sample Preconcentrationmentioning
confidence: 99%
“…Pervaporation has been coupled online to CE using a simple interface (a modified CE vial) that allowed volatile analytes (e.g., HSO À 3 ) to be isolated and interferences from complex matrices thus avoided [88]. Another option when the performance of a CE system can be improved at the stage of sample introduction concerns the application of flow injection (FI)-CE systems [89].…”
Section: Sample Preconcentrationmentioning
confidence: 99%
“…It was found that using 28 mL of water for SD resulted in collecting about 25 mL of distillate, therefore this volume of the sample after distillation was obtained in further studies. These volumes ensured that all the analyte was transferred to the distillate, hence, unlike other methods [21][22][23][24][25][26][27][28], there was no need to calibrate the system. There was no significant difference observed between the results obtained for different sample volumes, but due to the low relative error of the obtained results and better precision, sample volume of 6 mL was selected.…”
Section: Step Sv I Position Sp I Flow Ratementioning
confidence: 99%
“…Many flow-based methods were developed to determine titratable acidity in wines [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, only a few of them were simultaneously adapted to VA determination [21][22][23][24][25][26][27][28]. The procedure of VA determination is laborious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations